2014
DOI: 10.1380/ejssnt.2014.230
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of TiN/MgO Interfaces

Abstract: TiN(001)/MgO(001) interfaces have been investigated by using the total energy pseudopotential method. Their relaxed interface structures and electronic properties (charge densities, electronic band structures, density of states, etc.) were obtained. All the calculated electronic states of the TiN/MgO interfaces correspond to metallicity. Upon full structural relaxation of these interfaces, the cation (Ti) and anion (N) atoms on the interface layer are rumpled. This trend of atomic displacements at the interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…It was found that the interface with cation-anion bonding configurations (namely, Ti-O and Mg-N) is energetically favorable for TiN(0 0 1)/ MgO(0 0 1) interfaces which agree well with other reported theoretical results [16,17] and the interface with N(Ti) atoms located above bridge sites between Mg(O) atoms of TiN(1 1 0)/ MgO(1 1 0) interfaces shows the largest adhesion energy; in addition, the orientation relationship has a significant impact on the stability of the interface, which can account for the substantial effect of the substrate on the growth direction of nanowires [10]. By applying some analytical methods, we characterized the interfacial electronic structure.…”
Section: Introductionsupporting
confidence: 89%
“…It was found that the interface with cation-anion bonding configurations (namely, Ti-O and Mg-N) is energetically favorable for TiN(0 0 1)/ MgO(0 0 1) interfaces which agree well with other reported theoretical results [16,17] and the interface with N(Ti) atoms located above bridge sites between Mg(O) atoms of TiN(1 1 0)/ MgO(1 1 0) interfaces shows the largest adhesion energy; in addition, the orientation relationship has a significant impact on the stability of the interface, which can account for the substantial effect of the substrate on the growth direction of nanowires [10]. By applying some analytical methods, we characterized the interfacial electronic structure.…”
Section: Introductionsupporting
confidence: 89%
“…The lattice mismatch of TiN and MgO is 1.4%. [20] are also tabulated. Their electronic states ("Metal", "Semimetal", and "Semiconductor") are tabulated.…”
Section: Resultsmentioning
confidence: 99%
“…A partial core correction (PCC) [31] is considered for the Sc, Ti, V, Nb, and Mg pseudopotentials. Two types of Mg pseudopotentials were prepared in the previous study [20]. In this study we chose the Mg pseudopotential which is more suitable for the TiN/MgO superlattice with a smaller lattice mismatch of TiN and MgO.…”
Section: Methods Of Calculationmentioning
confidence: 99%
See 2 more Smart Citations